Regional Differentiation in Probability of Ice Days Occurrence in Poland - Łupikasza, Ewa; Niedźwiedź, Tadeusz; Małarzewski, Łukasz (Quaestiones Geographicae, 2014)
This paper aims at recognizing spatial differentiation in probability of ice days occurrence with reference to atmospheric circulation, using regional classification of circulation types for Poland. Daily maximum air temperatures measured at nine meteorological stations were used to recognize the ice days occurrence in the period from January 1951 to March 2014. The relations between the ice days occurrence and atmospheric circulation were analysed using catalogues of circulation types compiled for nine grid boxes within Poland. Linkage between the frequency of ice days and atmospheric circulation was recognized in the period of January 2001 - March 2014. A decreasing tendency in the frequency of the occurrence of winter ice days was found. The occurrence of ice days in Poland is clearly related to atmospheric circulation. In the entire area of Poland their occurrence is favoured by eastern and south-eastern advection of air during anticyclonic conditions (types Ea nad SEa). Regional variability is also noticeable.